Comparative Technical-Economical Analysis of Transient Stability Improvements in a Power System - Giuseppe Marco Tina; Giovanni Maione; Sebastiano Licciardello; Domenico Stefanelli (Applied Sciences, 2021)
Power systems are rapidly evolving to face the increasing penetration of renewable inverter-based generation units and to improve their reliability and safety. A power system is constantly exposed to sudden changes or disturbances that may affect its stability. In this paper, a comparative analysis of solutions to improve transient stability, both rotor angle and frequency stability, is performed. These solutions are SVC, STATCOM, a fast excitation system, and an additional parallel transmission line. Sensitivity analyses were performed to evaluate the effects of the location of the three-phase fault line and the most effective SVC or STATCOM installation bus. Based on these analyses, the worst-case fault is considered, and the critical fault clearing time is determined as an engineering parameter for comparing the different solutions. For the numerical analysis, the IEEE 9 bus system is considered, and the PowerWorld software tool is used. Rotor angle and frequency stability analyses were performed. Moreover, specifically for SVC and STATCOM, the effects of different values of short-circuit ratios were considered in the context of rotor angle stability analysis. As part of the frequency stability analysis, the use of the remuneration for load shedding service in Italy was considered to perform an economic analysis for SVC and STATCOM.